Peer teaching enhances basketball dribbling skills in an indonesian junior high school extracurricular program - Nurliani, Nurliani; Asyhari, Hasbi; Kuswoyo, Dilli Dwi; Roldan, Patrick John B. (Universitas Tanjungpura, 2026)
Background Peer teaching may facilitate active participation and collaborative learning during extracurricular sports instruction. However, evidence concerning its implementation in basketball dribbling instruction among Indonesian junior high school students remains limited. Objectives This study aimed to describe the implementation of peer teaching and changes in cognitive, affective, and psychomotor learning outcomes during basketball dribbling instruction in a junior high school extracurricular program. Methods A two-cycle classroom action research design was conducted with 25 basketball extracurricular participants at UPT SPF SMP Negeri 5 Makassar, Indonesia. Each cycle involved planning, action, observation, and reflection. Students with comparatively stronger basketball competence were assigned as peer tutors to demonstrate dribbling techniques, guide practice, and provide feedback to their classmates. Data were collected using observation sheets, documentation, and assessments covering cognitive, affective, and psychomotor learning outcomes. The available data were analyzed descriptively using mastery frequencies and percentages. Results Observations during Cycle I indicated increased participation, although several students continued to experience difficulty controlling the ball while moving, and some peer tutors required additional teacher guidance. Numerical mastery data for Cycle I were unavailable; therefore, the magnitude of change between cycles could not be calculated. Following instructional refinement in Cycle II, all 25 students achieved mastery in the cognitive domain (100%) and affective domain (100%). In the psychomotor domain, 23 students achieved mastery and two did not, resulting in a mastery rate of 92%. Students also demonstrated greater confidence, collaboration, participation, and technical control during dribbling practice. Conclusion Peer teaching was associated with high cognitive, affective, and psychomotor mastery levels by the end of Cycle II and may support active and collaborative basketball instruction. However, because numerical baseline and Cycle I results, inferential analyses, and a control group were unavailable, these findings are limited to this classroom action research context and should not be interpreted as causal evidence of effectiveness.